Exploring High School Students' Concept Mastery of Work and Energy Topics: A Quantitative Descriptive Study with Insights for STEM Learning - Maharani Karunia Putri; Parno Parno; Nuril Munfaridah; Marlina Ali (Jurnal Pendidikan Sains, 2023)
This quantitative descriptive study investigates the concept mastery of work and energy among high school students, specifically focusing on 105 students from the XI MIPA Laboratory UM High School. The research employs a concept mastery test, adapting Bloom's taxonomy indicators from C2 to C6, comprising 15 reasoned multiple-choice questions with a reliability value of 0.704. Student responses, categorized into No Response (NR), No Understanding (NU), Incorrect Understanding (IU), Partial Understanding (PU), and Sound Understanding (SU), reveal a prevalent mastery level in the category of Incorrect Understanding or partial comprehension of misconceptions. Specifically, NR, NU, IU, PU, and SU categories are reported at 4.76%, 39.05%, 52.38%, 3.81%, and 0%, respectively. Subtopics such as work-potential energy and kinetic energy-conservation of mechanical energy law fall within the IU and NU categories. The findings emphasize the need for a tailored learning model addressing misconceptions and aligning scientific explanations with everyday experiences. This study underscores the importance of incorporating learning cycle methodologies, STEM approaches, and formative assessment strategies to enhance students' comprehension of work and energy concepts.DOI: 10.17977/jps.v11i22023p056